Dual antidiabetic and antihypertensive activity of fucoxanthin isolated from Sargassum wightii Greville in in vivo rat model - Vijayan Raji; Chitra Loganathan; Thiyagarajan Ramesh; Palvannan Thayumanavan (Food Science and Human Wellness)
In a previous study from our laboratory, fucoxanthin purified from brown algae, Sargassum wightii Greville has found to exhibit antioxidant activity and inhibition of angiotensin-I-converting enzyme (ACE) in vitro. The present study aims in understanding the protective effect of fucoxanthin purified from S. wightii against diabetes with hypertension in in vivo. Diabetes and hypertension were induced in rat by streptozotocin and sodium chloride treatment, respectively. In diabetes with hypertension rat, the blood pressure was increased along with hyperglycemia. Administration of fucoxanthin significantly reduced the blood pressure and ACE activity in diabetes with hypertension rat. Furthermore, administration of fucoxanthin significantly reduced the hyperglycemic state. The activity of various enzymes in the liver (hexokinase, glucose-6-phosphate dehydrogenase, glucose-6-phosphatase and fructose-1,6-phosphatase) and serum (creatine kinase) were normalized to that of control level. The level of glycogen, glycoprotein component and lipid profile were equivalent to control level by fucoxanthin administration in diabetes with hypertension rats. Fucoxanthin ameliorated the oxidative stress by preserving the endogenous antioxidant levels in diabetes with hypertension rats. Also, the pancreatic histological integrity was similar to that of control level in diabetes with hypertension rats by fucoxanthin treatment. Altogether, fucoxanthin showed dual antidiabetic and antihypertensive activity in vivo.